Recognition of Autistic Children Knowledge through Language Input in Classroom Interaction - Andarwulan, Trisna; Ibrahim, Abd. Syukur; Suparno,; Martutik, (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to investigate the recognition of autistic children knowledge through the provision of language input in classroom interactions. Specifically, research on the recognition of autistic children's knowledge through language input can be elaborated into three things, they are (1) providing teacher language input in classroom interactions; (2) cognitive knowledge of autistic children based on the provision of teacher language input; and (3) the language knowledge of autistic children based on the teacher's language input. The results showed that the ability of knowledge recognition of each autistic child varies even though they are on the same level. Education and age are not always the main factors in the cognitive level of autistic children. The cognitive level and language knowledge of Class VI students are not always better than grade V students, the evident can be seen from Student 3 (S3) in six grades. The cognitive abilities and language knowledge of S3 are no better than Student 2 (S2). However, the recognition of knowledge of autistic children can be good if the language input provided by the teacher is done correctly. The provision of language input through interrogative, imperative, and declarative speech the teacher is able to recognize factual, conceptual, and procedural knowledge of autistic children.